La narrativité musicale - Michael Toolan (Cahiers de Narratologie)
Instrumental musical composition is usually excluded from the broad church of potentially narrative forms (cartoons, mime, ballet, stained glass windows, along with the prototypical exemplars). I discuss some of the ways in which music may still, on some and perhaps most occasions, be judged to be endowed with narrativity. Narratives typically have events, plot, characters, a setting or situation. Additionally there is often a favouring of linguistic-propositional meaning-representations in narratological analyses, which inevitably sends non-linguistic forms (music, painting, mime) to the margins of consideration. Thus even if, charitably, we think of particular instruments as voices and by implication as ‘characters’, participating in ‘events’ experienced in sequence, there remains the difficulty or inappropriateness of verbal description of those characters and the events in which they figure. ‘Plot’ seems a particular stumbling block to the assimilating of instrumental music to other narrative forms. But some of our problems may stem from expecting one kind of representation (linguistic, propositional) in narratives, when other kinds, found in music as in narrative paintings, are valid although unverifiable.